2020
DOI: 10.3389/fmicb.2020.01274
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Phosphorylation Controls Carbon Source Utilization and Virulence of Candida albicans

Abstract: Candida albicans is an opportunistic human fungal pathogen that relies upon different virulence traits, including morphogenesis, invasion, biofilm formation, and nutrient acquisition from host sources as well as metabolic adaptations during host invasion. In this study, we show how sugar kinases at the start of glycolysis modulate virulence of C. albicans. Sequence comparison with Saccharomyces cerevisiae identified four enzymes (Hxk1, Hxk2, Glk1, and Glk4) in C. albicans with putative roles in sugar phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 71 publications
3
8
0
Order By: Relevance
“…In a previous study [ 13 ], we showed that the hexokinase Ca Hxk2 is essential for fitness and virulence in C. albicans , which was reconfirmed by the work of Wijnants et al [ 14 ]. Glucose phosphorylation by Ca Hxk2 is not only necessary for glucose metabolism, but is also a key step for filamentation, stress response, macrophage and Galleria melonnella infection [ 13 ].…”
Section: Introductionsupporting
confidence: 64%
“…In a previous study [ 13 ], we showed that the hexokinase Ca Hxk2 is essential for fitness and virulence in C. albicans , which was reconfirmed by the work of Wijnants et al [ 14 ]. Glucose phosphorylation by Ca Hxk2 is not only necessary for glucose metabolism, but is also a key step for filamentation, stress response, macrophage and Galleria melonnella infection [ 13 ].…”
Section: Introductionsupporting
confidence: 64%
“…The occurrence of several hexose kinases is common among living organisms. Hence, higher plants and fungi generally possess both hexokinases and glucokinases, where they catalyze the first step of glucose metabolism but also play a major role in glucose sensing signal transduction, development, growth, cell death, and hormone pathways [90][91][92], with distinct enzymatic properties and even separate functions [93][94][95][96]. In these cases, glucokinases may even be devoid of catalytic activity, whereas the canonical hexose activity is mediated by the hexokinase.…”
Section: Discussionmentioning
confidence: 99%
“…While the gene drive platform allows for rapid, high-throughput generation of mutant libraries in C. albicans , CRISPR-Cas9 also enables the generation of higher-order mutants beyond pairwise gene mutations. Recent work by Wijnants et al used CRISPR-Cas9 to characterize putative sugar phosphorylation genes in this manner, demonstrating how different combinations of genes affected cell metabolism and virulence in a murine model (Wijnants et al, 2020 ). Double, triple, and quadruple mutants of putative C. albicans sugar kinase genes ( HXK1, HXK2, GLK1 , and GLK4 ), were generated using a CRISPR marker-recycling system.…”
Section: Applications Of Crispr In Candidamentioning
confidence: 99%
“…Meanwhile, hxk1 mutants formed the weakest biofilms, despite comparable adhesion levels to the wild type. The reduced virulence of all the other hxk1 mutants, given their weak biofilm formation but hyperfilamentous phenotypes, alludes to the interplay between morphogenesis and glycolytic metabolism in orchestrating a systemic infection (Wijnants et al, 2020 ). This is a powerful study that used higher-order mutants to decouple adherence mechanisms, robust biofilm formation, and virulence, which provides clearer insight into multiple interconnected pathways in C. albicans .…”
Section: Applications Of Crispr In Candidamentioning
confidence: 99%